Modality And Region-Oriented Medical Image Compression Using Wavelets - Sarina Mansor, (2003)
Medical image compression is becoming increasingly important with the emergence of telemedicine applications. The need for data compression is crucial for storage and transmission purposes since the medical images are inherently voluminous, much more bulky than the usual images sent over the internet. One of the popular compression techniques to use wavelets. Wavelets complement the shortcomings of JPEG and are better matched to the human visual system (HVS) characteristics.